1994
DOI: 10.1042/bj2990695
|View full text |Cite
|
Sign up to set email alerts
|

Blue shifts in bacteriochlorophyll absorbance correlate with changed hydrogen bonding patterns in light-harvesting 2 mutants of Rhodobacter sphaeroides with alterations at α-Tyr-44 and α-Tyr-45

Abstract: A combination of Fourier-Transform (FT) resonance Raman spectroscopy and site-directed mutagenesis has been used to examine the function of two highly conserved aromatic residues, alpha-Tyr-44 and alpha-Tyr-45, in the light-harvesting 2 (LH2) complex of the photosynthetic bacterium Rhodobacter sphaeroides. In LH2 complexes, aromatic residues located at positions alpha-44 and alpha-45 are thought to be located near the putative binding site for bacteriochlorophyll, and alterations at these positions are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
175
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(188 citation statements)
references
References 21 publications
13
175
0
Order By: Relevance
“…From these studies, for example, it has been shown that each H-bond breakage between the apoproteins and the acetyl carbonyl oxygens of the B850 molecules correlates with a 10 nm blue shift of the absorption maximum [9]. A similar e¡ect also occurs with the B800 molecules.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…From these studies, for example, it has been shown that each H-bond breakage between the apoproteins and the acetyl carbonyl oxygens of the B850 molecules correlates with a 10 nm blue shift of the absorption maximum [9]. A similar e¡ect also occurs with the B800 molecules.…”
Section: Introductionmentioning
confidence: 97%
“…Here, we have compared the Bchla-protein interactions in native and Bchla-reconstituted complexes by resonance Raman spectroscopy. The Raman spectra of LH2 complexes have previously been shown to be very sensitive to the environment of the Bchla molecules [6,9,10]. This allowed us to use this technique to assess whether or not the Bchla molecules are correctly bound within the reconstituted complex.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the α-Trp-45 is hydrogen-bonded to the 2-acetyl group of BChla. However, there is no direct information about which of the two B850 BChla's is involved in such a hydrogen bond [FSRH94]. Based on the optimized tertiary structure for both α and β subunits,we found that it is more feasible spatially to form an inter-unit hydrogen bond, i.…”
Section: Construction Of the Complete Octamermentioning
confidence: 98%
“…rubrum on the cytoplasmic side of the membrane by partial hydrolysis with proteolytic enzymes [BWS + 84], both α-and β-polypeptides should be oriented with their N-terminals towards the cytoplasm; (2) strong circular dichroism (CD) signals suggest exciton interactions between pairs of BChla molecules [Zub93]; (3) linear dichroism data indicate that the B850 BChla's are approximately perpendicular to the membrane and the B800 BChla is parallel to the membrane [KvGH + 84]; (4) Fourier-transform Resonance Raman spectroscopy and site-directed mutagenesis [FSRH94] of a related lightharvesting complex indicate that another highly conserved residue, α-Trp-45, is hydrogen-bonded to the 2-acetyl group of BChla. All these observations impose constraints on the structure.…”
Section: Vhm90 Sld + 90]mentioning
confidence: 99%
“…850 nm ; hence the alternative names for LH1 and LH2 of B875 and B800-850 respectively. These antenna complexes were also subjected to extensive spectroscopic analysis and genetic manipulation by site-directed mutagenesis (Youvan et al, 1985 ;Burgess et al, 1988 ;Bylina et al, 1988 ;Coleman & Youvan, 1990 ;Fowler et al, 1992Fowler et al, , 1994Jones et al, 1992a ;Hunter, 1995), as a result of which several structural models were proposed. The development of ideas about the structure and function of these antenna complexes is the subject of two reviews by Hunter and co-workers (Hunter et al, 1989 ;Olsen & Hunter, 1994).…”
Section: The Structure Of Antenna Complexesmentioning
confidence: 99%